NGINX HTTP server harness the power of NGINX with a series of detailed tutorials and real-life examples - Ouiran, Gabriel; Nedelcu, Clément; Fjordvald, Martin Bjerretoft (Packt Publishing Ltd., 2024)
Explore the capabilities of NGINX, a robust HTTP server designed for handling high-traffic websites, with network scalability as its primary objective. Whether you're a beginner or an experienced administrator, this NGINX book will guide you through the complete process of setting up this lightweight HTTP server, from quick and basic configurations to more detailed configurations tailored to your needs. Highlighting the latest version 1.25.2, featuring new features such as HTTP/3 and QUIC, this edition keeps you up to date with cutting-edge developments. This book is packed with a multitude of real-world examples, which will help you secure your infrastructure with automatic TLS certificates, expertly place NGINX in front of your existing applications, and do much more. From orchestration and Docker to bandwidth management, OpenResty, and NGINX Plus commercial features, you'll get to grips with enhancing and optimizing your infrastructure or designing brand-new architecture. Moreover, this updated edition will show you how NGINX excels in cloud environments with guides on integrating NGINX with cloud services for deploying scalable architectures efficiently and securely. By the end of this book, you'll be able to adapt and use a wide variety of NGINX implementations to tackle diverse challenges with confidence.
Includes index
Keywords: Web servers -- Computer programs; HTTP (Computer network protocol); Open source software; Serveurs Web; Logiciels; HTTP (Protocole de réseaux d'ordinateurs); Logiciels libres